THE IMPLEMENTATION OF PUBLIC INFORMATION DISCLOSURE THROUGH PEOPLE'S ONLINE COMPLAINTS INTEGRATED ON INFORMATION AND SERVICES CENTER IN MEDAN STATE UNIVERSITY, INDONESIA - M. Surip; Hendra Kurnia Pulungan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
The People's Aspiration Service and the People's Online Complaints (LAPOR) and Integrated Information and Service Center  are the two flagship programs of the Medan State University Information and Documentation Management Officer (PPID). These two programs are an effort to follow up on Law Number 14 of 2008 concerning Public Information Openness. The program is also an effort of Unimed in supporting the creation of Good Governance especially in the field of higher education services. This study aims to find out how the implementation of LAPOR  programs on public information disclosure in Unimed. This type of research is descriptive qualitative. The focus of this research is implementation, access, mechanisms and constraints. Policy implementation is implemented to achieve the objectives of an institution. At the policy implementation stage, the policies that have been made or determined will be implemented, however, the implementation phase of this policy is the most severe stage, this is because in implementing or implementing a policy will certainly experience various kinds of problems in the field. Public information disclosure is regulated in Law No. 14 of 2008 concerning Public Information Openness (UU KIP).